Application of the Creative Problem Solving (CPS) Learning Model to Improve Students' Mathematical Problem-Solving Ability - Batu, Siti Salwia (Holistic Science, 2023)
This study aims to improve the ability to solve students' mathematical problems through the application of the Creative Problem Solving (CPS) learning model. This research was conducted at MTs Muhammadiyah Al-Fatah Nangahale in the even semester of the 2021/2022 school year. The subject of this research is class VIII students. The method used in this study is quantitative descriptive through classroom action research with 2 cycles. The ability to solve the mathematical problem of students by applying the CPS learning model to the circle material is good. This is evidenced by the value of students who reach the KKM value. It can be concluded that the CPS learning model improves the ability to solve mathematical problems in class VIII students at MTs Muhammadiyah Al-Fatah Nangahale. This can be seen the results of the test that is increasing in each cycle, namely the average value of the 58.3 cycle to 80.6 in the second cycle. Cycle I 20% of students get a value above the KKM score, while in the second cycle 85% of students get a score above the KKM